KINERJA KARYAWAN RS. BHAYANGKARA TK 1 R. SAID SUKANTO DIPENGARUHI OLEH KEPEMIMPINAN MELALUI BUDAYA ORGANISASI - Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The research objective to be achieved is to determine the influence of leadership on the performance of employees Hospital Bhayangkara Tk. I R. Said Sukanto through organizational culture. This study uses quantitative methods. The population in this study were employees Hospital Bhayangkara Tk. I R. Said Sukanto, East Jakarta. The technique used for sampling is simple random sampling. Before testing the hypothesis, the data instrument is first tested, the data analysis method uses path analysis. The results of the stud: leadership has a positive and significant indirect effect on the performance of employees Hospital Bhayangkara Tk. I R. Said Sukanto East Jakarta through organizational culture.